2013
DOI: 10.1007/s00213-013-3148-z
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment

Abstract: These findings suggest that chronic heroin use induces long-lasting striatal DAT reductions. DAT availability remained unchanged during a 6-month period of abstinence. Treatment with Jitai appears to be effective at increasing striatal DAT availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…This right-greater-than-left asymmetry has been reported in previous studies where healthy people were found to have the right-greater-than-left asymmetry in D 2 receptor and DAT availability in the caudate (Laakso et al 2001;Tomer et al 2008). Moreover, several imaging studies in opioid or methamphetamine dependent subjects and healthy controls also found a slight right-great-than-left asymmetry in DAT levels in the striatum Liu et al 2013;Shi et al 2008;Yuan et al 2014). Nevertheless, no significant differences in these right-greater-than-left asymmetries were reported.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This right-greater-than-left asymmetry has been reported in previous studies where healthy people were found to have the right-greater-than-left asymmetry in D 2 receptor and DAT availability in the caudate (Laakso et al 2001;Tomer et al 2008). Moreover, several imaging studies in opioid or methamphetamine dependent subjects and healthy controls also found a slight right-great-than-left asymmetry in DAT levels in the striatum Liu et al 2013;Shi et al 2008;Yuan et al 2014). Nevertheless, no significant differences in these right-greater-than-left asymmetries were reported.…”
Section: Discussionmentioning
confidence: 91%
“…Previous clinical trials have documented the efficacy of JTT at inhibiting withdrawal symptoms and restoring the physiological functions altered by chronic drug use (Xu et al 2000;Zihong et al 2007). A prior study from our laboratory also documented that striatal DAT availability remained at reduced levels in heroin-dependent subjects during a 6-month period of abstinence, and treatment with JTT led to increased DAT after 6 months (Liu et al 2013). However, whether striatal DAT levels can be normalized after longer period of abstinence, and whether JTT treatment longer than 6 months could induce a further increase in DAT and improve neuropsychological functions remains unknown.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations